2020
DOI: 10.2147/cmar.s234586
|View full text |Cite
|
Sign up to set email alerts
|

<p>Down-regulation of USP8 Inhibits Cholangiocarcinoma Cell Proliferation and Invasion</p>

Abstract: Objective: Cholangiocarcinoma is the second most common primary hepatobiliary malignancy with high incidence and recurrence rate. Ubiquitin-specific protease 8 (USP8) is recently reported to be involved in tumor progression. Herein, we aimed to investigate the effects of USP8 on the growth and metastasis abilities of cholangiocarcinoma cells. Methods: The siRNA interference was used to knock down USP8 in cholangiocarcinoma cell lines QBC939 and RBE; Hucct-1 cells were transfected with pcDNA3.1-USP8 to upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The oncogenic role of USP8 in other cancers, such as lung cancer, cervical cancer and Cholangiocarcinoma, have been reported. 6–8 Our work together with the previous reports suggest that USP8 is a novel therapeutic target for cancer.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The oncogenic role of USP8 in other cancers, such as lung cancer, cervical cancer and Cholangiocarcinoma, have been reported. 6–8 Our work together with the previous reports suggest that USP8 is a novel therapeutic target for cancer.…”
Section: Discussionsupporting
confidence: 66%
“…5 Ubiquitin-specific protease 8 (USP8), one of USP family member, has been recently revealed to play important roles in cancer progression, metastasis and drug resistance. [6][7][8][9] USP8 interacts with Cdc25, Nrdp1, ErbB2 and epithelial growth factor receptor (EGFR), which are all clinically relevant cancer targets. USP8 knockout mice display significant growth retardation and marked downregulation of several receptor tyrosine kinases (RTKs), including EGFR, c-Met and ErbB3.…”
Section: Introductionmentioning
confidence: 99%
“…25 Oncogenic function of USP8 is also observed in gastric cancer, cholangiocarcinoma, and breast cancer. [26][27][28] Apart from them, a growing body of evidence has demonstrated the tumor-promoting role of USP5 in different cancer types. 8,10,11,[13][14][15] And in this study, we found that it was also the case in UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of USP8 promotes intrinsic apoptosis by suppressing AKT activity in cholangiocarcinoma (CCA) [ 79 ]. USP8 promotes both the stabilization and destabilization of c-FLIP, an anti-apoptotic protein.…”
Section: Dubs Regulating Diverse Rcdmentioning
confidence: 99%